Pengaruh pemberian inokulan Burkholderia cenocepacia dan bahan organik terhadap sifat fisik tanah berpasir Effect of the inoculation of Burkholderia cenocepacia and organic materials on physical properties of a sandy soil - Laksmita Prima SANTI; . SUDARSONO; Didiek Hadjar GOENADI; Kukuh MURTILAKSONO; Dwi Andreas SANTOSA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2010)
AbstractSoil aggregation is a dynamic and very important factor for the development of agricultural soil functions. Unstable soil aggregation in a sandy soil type is a limiting factor for plant growth. The aim of this study was to investigate theinfluence of a exopolysaccharide-producing bacterium and organic material on some physical properties of a sandy soil. A highly potential bacterium for exopolysaccharides production, i.e Burkholderia cenocepacia, was isolated froma sandy soil located at Kotawaringin Barat, Central Kalimantan. The isolated bacterium is capable on improving aggregate’s stability of a soil with about 60% sand fraction [medium sand fraction (MSF)]. Interaction between available water and electric conductivity with aggregate stability index has significant correlation in medium sand fraction inoculated by 109 CFU of B. cenocepacia suspension, i.e. r = 0.806* and r=0.966**, respectively. Organic materials and its combination with the addition of 108 CFU B. cenocepacia suspension treatments could increase the aggregate stability index but have no effects on bulk density and total pore space values in an artificial condition of medium sand fraction. AbstrakAgregasi tanah bersifat dinamis dan merupakan faktor penting untuk pengembangan fungsi tanah pertanian. Ketidakstabilan agregat tanah pada jenis tanah berpasir merupakan faktor pembatas untuk pertumbuhan tanaman.Penelitian ini bertujuan untuk mengetahui pengaruh eksopolisakarida bakteri dan bahan organik terhadap beberapa sifat fisik bahan tanah berpasir. Satu bakteri potensial penghasil eksopolisakarida yaitu Burkholderia cenocepacia telah berhasil diisolasi dari bahan tanah berpasir asal Kotawaringin Barat, Kalimantan Tengah. Bakteri ini dapat meningkatkan kemantapan agregat bahan tanah dengan kandungan fraksi pasir sekitar 60% [fraksi pasir sedang (FPS)]. Hubungan antara air tersedia dan konduktivitas elektrik terhadap indeks kemantapan agregat sangat nyata pada bahan tanah FPS yang diinokulasi dengan 109 CFU suspensi B. cenocepacia masing-masing r = 0,806* dan = 0,966**. Perlakuan bahan organik dan kombinasinya dengan penambahan 109CFU suspensi B. cenocepacia dapat meningkatkan indeks kemantapan agregat tetapi tidak mempengaruhi nilai kerapatan lindak dan total ruang pori di dalam fraksi pasir sedang.